Mathematical Literacy: A Case Study on Padang Students' Mathematical Ability - Yulia, Yulia; Kustati, Martin; Afriadi, Juli (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
This study aims to analyze student mathematical literacy ability from the perspective of students' Mathematical Ability. This research is a descriptive study with a qualitative approach. The research subjects were three students of XI IPA 1 MAN 1 Padang with different mathematical abilities: low, medium, and high. Data were collected through documentation, tests, and interviews. The results of the analysis show that students with high abilities can solve routine problems, interpret problems and solve them with formulas, carry out procedures well, can deal with complex situations, use their reasoning in solving problems, can work effectively and interpret different representations and then relate them to the real world. Students with moderate abilities can solve routine problems, interpret problems and solve them with formulas, and carry out procedures properly. Meanwhile, students with low abilities are only able to solve routine questions. Based on these results, it is necessary to look for strategies in the mathematics learning process, which enable the improvement of students' mathematical literacy skills.